Taekwondo training speeds up the development of balance and sensory functions in young adolescents - Fong, S. S. M.; Fu, S.; Ng, G. Y. F. (Journal of Science and Medicine in Sport, 2012)
Objectives: This study aimed (1) to identify the developmental status of balance and sensory functions in young adolescents as compared to adults and, (2) to explore the effect of Taekwondo (TKD) training on the development of balance and sensory systems in young adolescents. Design: Cross-sectional controlled trial. Methods: Sixty-six participants including 42 adolescents (21 TKD practitioners, 21 non-TKD practitioners) and 24 adults were tested. The sway velocity of centre of gravity was recorded during standing on the non-dominant leg on a Smart Equitest ® system. The somatosensory, vestibular and visual ratios were also measured with the machine. Results: Adult participants swayed slower than both TKD and non-TKD adolescent groups during single leg stance with eyes open (p = 0.007 and p < 0.001, respectively). The TKD adolescent group, in turn, swayed slower than the non-TKD adolescent group (p < 0.001). Adult participants had better visual ratio than both TKD and non-TKD adolescents (p = 0.001 and p < 0.001, respectively) while there was no difference between the TKD and non-TKD adolescents (p = 0.164). For the vestibular ratio, there was no significant difference between adult participants and TKD adolescents (p = 0.432). Adolescents who did not practice TKD showed significantly lower vestibular ratio than TKD adolescents and adults (p = 0.003 and p < 0.001, respectively). In addition, there was no significant difference in the somatosensory ratio among the 3 participant groups (p = 0.711). Conclusions: Participation in TKD appears to speed up the development of postural control and vestibular function in adolescents. Clinicians might advocate TKD exercise as a therapeutic intervention for young people with balance or vestibular dysfunctions.